Cuba, the Island that is not Forgotten or Forgiven (Docentes 2.0 Journal, 2024)
Cuba is an island archipelago state in the Caribbean Sea. Colony of Spain until 1869, then under the protectorate of the United States lived a turbulent 20th century after the triumph of its revolution in 1959. One of the protagonists of the Cold War. Such events condemned him to neither be forgotten nor forgiven in the development of contemporary history. This research aimed to describe the experiences of a research internship with a group of professionals from Ayacucho, Peru. The research was based on the method of observation and analysis of texts, phenomenological and hermeneutical paradigms, with a qualitative approach, ethnographic design, and basic type whose record was left in a field diary. The process was observed and participated with a group of teachers from the Faculty of Social Sciences and Education. The pedagogical and research experiences occurred mainly at the Universidad de Oriente in Santiago de Cuba. After verifying the data and categories observed on the island, it was concluded that it continues with high revolutionary morale in constructing a new political, economic, and social system. Evidence of this is in his practice of Marxist humanism and his dedication to research as a priority of the educational system.
Keywords: Revolutionary morality; neither forgetting nor forgiving